The challenge of crime rethinking our response - Ruth, Henry S. (Harvard Univ. Press, 2003)
"This book examines the history, scope, and effects of the revolution in America's crime response since 1970. Henry Ruth and Kevin Reitz offer a comprehensive, long-term, pragmatic approach to increase public understanding of and find improvements in the nation's response to crime. Concentrating on meaningful areas for change in policing, sentencing, guns, drugs, and juvenile crime, they discuss such topics as new priorities for the use of incarceration; aggressive policing; the war on drugs; the need to switch the gun control debate to a focus on crime gun regulation; a new focus on offenders' transition from confinement to freedom; and the role of private enterprise."--BOOK JACKET.